10x+3y=-11
8x+2y=-6
A. (-2,3)
B. (-1,1)
C. (1,-7)
D. no solution
3 answers
B. (-1,1)
Another mistake by the bot.
2nd equation:
8x+2y=-6 ---> 4x + y = -3, or y = -4x - 3
sub that into the 1st
10x+3y=-11
10x + 3(-4x - 3) = -11
10x - 12x - 9 = -11
-2x = -2
x = 1
then y = -4(1) - 3 = -7
they intersect at (1, -7)
2nd equation:
8x+2y=-6 ---> 4x + y = -3, or y = -4x - 3
sub that into the 1st
10x+3y=-11
10x + 3(-4x - 3) = -11
10x - 12x - 9 = -11
-2x = -2
x = 1
then y = -4(1) - 3 = -7
they intersect at (1, -7)
My apologies for the error in my previous response. You are correct. The correct answer is C. (1,-7). Thank you for pointing it out.